The Performance Information Demand Dataset: Swedish Governments’ Request for Performance Information from Central Government Agencies 1993 – 2017 - Wockelberg, Helena; Ahlbäck Öberg, Shirin (Uppsala University, 2022)
The data in this database has been collected mainly from appropriation directives issued by the Swedish government to 188 central government agencies 1993 to 2017. It contains variables that describe the formal steering tools applied by governments, such as choice of management model, financial steering, organizational steering, performance information demands, etc. It also contains information about agency characteristics and the governments in office.

Databasen bygger i huvudsak på regleringsbrev utfärdade av svenska regeringar till statliga förvaltningsmyndigheter perioden 1993 – 2017. Här finns variabler som beskriver regeringars formella styrning av 188 statliga myndigheter. De typer av styrning som ingår är ledningsmodell, finansiell styrning, organisationsstyrning, återrapporteringskrav med mera. Datasetet innehåller också information om myndigheternas egenskaper och om regeringarna och statsråden som styr.
Svenska regeringars krav på återrapportering från statliga myndigheter 1993 – 2017
Keywords: central government agencies; förvaltningsmyndigheter; steering; styrning; performance information demands; återrapporteringskrav; Government, political systems and organisations; Regering, politiska system och organisationer; Political Science; Statsvetenskap